â€œAMBU-LINEâ€: AMBULANCE ONLINE TERPADU. INOVASI PELAYANAAN KESEHATAN UNTUK MENGURANGI RISIKO MORTALITAS AKIBAT KETERLAMBATAN RESPON - Adi, Galih Setia; Karimah, Rizqi Akhlaqul (Journal of Advanced Nursing and Health Sciences, 2020)
The important thing in pre-hospital emergency services is known as "The Golden Time). The faster the response, the better the results. It is reasonable to say that all efforts should be made to reduce the time factor in the alarm chain from calling to picking up the call, to sending, to getting ready to drive to the location of the survivor. This study aims to determine the effectiveness of ambu-line on patient transport. The research design used a Quasi Experimental research design with Pre Test and Post Test without Control Group. The sampling technique used purposive sampling with a sample size of 28 respondents. Test data analysis using Wilcoxon test. Wilcoxon test results showed that the P Value 0.34 <0.05. This shows that there is an effect of ambuline on the patient's response time.